EIGHT-STORY APARTMENT BUILDING DESIGN USING STEEL STRUCTURES WITH EBF (ECCENTRICALLY BRACED FRAME) STIFFENERS - Krisfanri Natanael Aritonang; Gati Annisa Hayu (Jurnal Rekayasa Sipil dan Lingkungan, 2020)
This research is about the design of steel structure building by using EBF stiffener. The purpose of this research is to design a high-level bulding of steel structures with EBF stiffener that is strong to withstand all the loads that work on the structure. The calculation method that used in this design include loads analysis and structural analysis that each folows the prevailing standards. SNI 1729:2015 is used for the design of steel structure (column and beam), SNI 2947:2013 for design of reinforced concrete structure (floor pelate), and also SNI 1726:2012 and SNI 1727:2013 are used for loading planning. The EBF design is designed using type of bracing “split K-braced” with the type of link is “intermediate link”. Structural analysis was performed using the structural software SAP 2000. The result of this research show that design with EBF stiffener is able to withstand all working loads. Penelitian ini adalah tentang perancangan bangunan struktur baja dengan menggunakan pengaku EBF. Tujuan dari penelitian ini adalah untuk merancang bangunan tingkat tinggi struktur baja dengan pengaku EBF yang kuat menahan seluruh beban yang bekerja pada sturktur. Metode perhitungan yang digunakan dalam perancangan ini antara lain analisis pembebanan dan analisis struktur yang masing-masing mengikuti standar yang berlaku. Digunakan SNI 1729:2015 untuk desain struktur baja (kolom dan balok), SNI 2847:2013 untuk desain struktur beton bertulang (pelat lantai), serta SNI 1726:2012 dan SNI 1727:2013 untuk perencanaan pembebanan. Desain EBF dirancang menggunakan tipe pengaku split K braced dengan tipe link adalah “intermediate link”. Analisis struktur dilakukan dengan menggunakan program struktur SAP 2000. Hasil dari penelitian ini menunjukkan bahwa seluruh desain struktur dengan pengaku EBF mampu menahan seluruh beban yang bekerja.